(untitled) (Journal of the College of Education for Women, 2019)
The grammar structure transforms from its fundamental field to another field that takes new dimensions, and is used in another way in speech that differs from the first one, because the formula basis of the name(Faael) in speech is a (distorted characteristic), and the distorted characteristic indicates the stability and the necessity of the characterized. as this characteristic has changed from its use as a distorted characteristic which was established by the elders. to a use that differs from the first and cannot be overlooked to achieve a new purpose, to be used as plural